Experience of non-breastfeeding mothers: Norms and ethically responsible risk communication - Fahlquist, Jessica Nihlén (Nursing ethics, 2016)
Background:Breastfeeding is currently strongly recommended by midwives and paediatricians, and the recommendations are based on documents provided by the World Health Organization and public health authorities worldwide.Research question:The underlying question is, how are non-breastfeeding mothers affected emotionally when informed that breastfeeding is the safest and healthiest option?Research design:The method used is an anonymous web-based qualitative survey exploring the narratives of non-breastfeeding mothers, published on Thesistools.com. The aim is to achieve qualitative knowledge about the emotions of non-breastfeeding mothers.Participants and research context:Participants were based in Sweden, the United Kingdom and the Netherlands and were selected through a purposeful sample.Ethical considerations:The online survey anonymizes responses automatically, and all respondents had to tick a box agreeing to be quoted anonymously in scientific articles. The study conforms to research ethics guidelines.Findings:Respondents describe how they were affected, and the following themes emerged in studying their descriptions: depression, anxiety and pain, feeling failed as a mother and woman, loss of freedom/feeling trapped, relief and guilt.Discussion:The themes are discussed against the background of the ethics of care and a theory of ethically responsible risk communication.Conclusion:Three conclusions are made. First, the message should become more empathetic. Second, information should be given in an attentive dialogue. Third, information providers should evaluate effects in a more inclusive way.